Altitudinal accumulation and diversity of leaf beetle (Coleoptera: Chrysomelidae) at Fraser’s Hill, Pahang - Muhaimin A. M. D.,; Norela Sulaiman,; Halim M.,; Yaakop S., (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
Most of the research on leaf beetles more focusing on their roles as a pest or biological control. On the ecological part is much understudied. So the objective of this study is to determine the accumulation and diversity of leaf beetles at different altitude on Fraser’s Hill, Pahang. Sampling was done in Dec 2016 – Feb 2017 at lower (<500 m a.s.l), middle (500-900 m a.s.l) and higher (>900 m a.s.l) altitudes by using sweep net from 10.00 a.m. to 2.00 p.m. A total of 296 individuals, 28 species and five subfamilies successfully collected. Galerucinae has the highest number of species and individuals with 14 and 154 respectively. Lower altitude has the highest individuals with 116 but has the lowest number of species with only 11. Meanwhile, sampling on Jan 2017 has the highest abundance of 108 individuals and 17 species. However, t-test indicates that there is no significant different between all Shannon index either by altitude-wise (H’ Higher = 1.80; Middle = 2.07; Lower = 1.95) or month-wise (H’ Dec ’16 = 2.36; Jan ’17 = 2.46; Feb ’17 = 2.32). Nevertheless, there is evidence showing that existence of species specificity towards altitude especially on the higher altitude which only one species that shared with middle altitude (Galerucinae sp. 1), while middle and lower shared more overlapped species. More intensive study must be done to view the distribution pattern more clear and detailed.